Functionalized MoS2-nanoparticles for transdermal drug delivery of atenolol - Kai Zhang; Yanling Zhuang; Weidan Zhang; Yali Guo; Xiaochang Liu (Taylor & Francis Group, 2020)
Molybdenum disulfide (MoS2) has excellent photothermal conversion abilities, an ultra-high specific surface area, and has been extensively explored for use in biomedicine. However, the high toxicity associated with MoS2 has limited its biological applications for in vivo photothermal therapy and drug delivery systems. Herein, we have developed cationic hydroxyethyl cellulose (JR400) surface-modified MoS2 nanoparticles (NPs) that are responsive to near-infrared (NIR) laser irradiation as a transdermal drug delivery system (TDDS). Herein, we confirmed the preparation of hexagonal phase MoS2 with robust surface modification with JR400. The flower-like morphology of the NPs had an average diameter of 355 ± 69.3 nm limiting the absorption of the NPs through the stratum corneum. With the ability to efficiently load 90.4 ± 0.3% of the model drug atenolol (ATE), where 1 g of JR400-MoS2 NPs was able to load 3.6 g ATE, we assayed the controlled release capacity in vitro skin penetration studies. These JR400-MoS2 NPs showed further enhancement under NIR stimulation, with a 2.3-fold increase in ATE skin penetration. Furthermore, we verified in vivo that these JR400-MoS2 NPs do not cause skin irritation suggesting that they are promising new TDDS candidates for small molecule drugs.